Rock mechanical properties of immature, organic-rich source rocks and their relationships to rock composition and lithofacies. Issue 1 (February 2023) - Abu-Mahfouz, Israa S; Iakusheva, Regina; Finkbeiner, Thomas; Cartwright, Joe; Vahrenkamp, Volker
No abstract available